2004
DOI: 10.1590/s1519-69842004000200019
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and genetic variability in natural populations of Anopheles (N.) triannulatus (Neiva& Pinto, 1922) of Brazilian Amazonia

Abstract: Populations of Anopheles triannulatus from Macapá (AP), Aripuanã (MT), Ji-Paraná (RO), and Manaus-Janauari Lake (AM) were studied using 16 enzymatic loci. The results of the isozyme analysis showed that the population of Macapá presented higher polymorphism (56.3%). The lowest variability was observed in the population of Manaus (p = 25.0; Ho = 0.077 +/- 0.046). The results of Wright's F statistics showed unbalance due to excess of homozygotes (F(is) > F(st)), denoting a certain intrapopulational differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…triannulatus populations into two groups, with Macapa-Amapa state in one group and Janauri Lake Manaus-Amazonas state, Ji-Paraná -Rondonia state and Aripuanã -Mato Grosso state in the other; the estimated low gene flow probably influenced the sub-population structure. 12 Cytochrome oxidase subunit I (COI) gene sequence analyses of specimens of An. triannulatus from northeast of the Amazon river, central and southern Brazil showed five groups with a significant signal of population expansion, suggesting that these populations were not at equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…triannulatus populations into two groups, with Macapa-Amapa state in one group and Janauri Lake Manaus-Amazonas state, Ji-Paraná -Rondonia state and Aripuanã -Mato Grosso state in the other; the estimated low gene flow probably influenced the sub-population structure. 12 Cytochrome oxidase subunit I (COI) gene sequence analyses of specimens of An. triannulatus from northeast of the Amazon river, central and southern Brazil showed five groups with a significant signal of population expansion, suggesting that these populations were not at equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…This shows the wide genetic variability in the Anopheles species and suggests that the variability is related to the innate population structure: mutation, preferential mating and selection or genetic drift. Moreover, previous studies 4 on Anopheles triannulatus populations in the Brazilian Amazon region revealed much smaller genetic distances (D = 0.011 -0.052). These data partially corroborate those reported by Sallum et al 40 , which were based on molecular characteristics, and by Harbach 41 based on morphological and molecular studies.…”
Section: Discussionmentioning
confidence: 73%
“…Among the molecular markers used in population genetic research, isoenzymes are used to estimate genetic variability, as well as for helping to elucidate problems that can occur in relation to morphological identification of species, especially given the existence of species complexes such as in the genus Anopheles [1][2][3][4][5] . The Anopheles albitarsis complex consists of six cryptic species 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Low polymorphism values were also detected in the An. triannulatus population from Lake Janauari (25 ≤ P ≤ 56.3, Brazilian Amazon, Santos et al 2004), in An. nuneztovari from Highway BR-174-AM, km 204 (P = 31.3, Brazilian Amazon, Scarpassa et al 1999), and An.…”
Section: Discussionmentioning
confidence: 99%
“…triannulatus and An. nuneztovari populations (Scarpassa et al 1999, Santos et al 2004) could be related to the fact that collection was performed during dry season, when breeding sites are drastically reduced, leading to mosquitoes population density decrease and favoring inbreeding, that could result in genetic drift or marginal effect and, selection. Low genetic variation was also found in An.…”
Section: Discussionmentioning
confidence: 99%